THE INFLUENCE OF THE INDONESIAN ORDER OF WORDS IN STUDIYING ENGLISH - H.M. Syadli Z.A. (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 1997)
The Influence of The Indonesian Order of Words in Studiying English